PENGARUH BRAND IMAGE, HARGA DAN FASILITAS TERHADAP KEPUTUSAN MAHASISWA MEMILIH KULIAH DI POLITEKNIK LP3I MEDAN KAMPUS MEDAN BARU - Sri Eka Wulandari; Amrin Fauzi; Arlina Nurbaity Lubis (Jurnal Dinamika Ekonomi & Bisnis, 2019)
Brand image, price, facilities and interest were factors that made students decided to study at Politeknik LP3I Medan Kampus Medan Baru. The objectives of the study were to find out and analize the effect of brand image, price, facilities and interest toward students’ decision to study at Politeknik LP3I Medan Kampus Medan Baru through interest as intervening variable. The respondents were 225 students. Simple random sampling was used as sampling technique. The data were analyzed by using path analysis. The result displayed that brand image, facilities had positive effect and significant to toward students. On the otherhand, price had negative effect toward students. The interest had positive effect and significant toward students’ decision to study at Politeknik LP3I Medan Kampus Baru. Brand image, facilities had positive effect and significant toward students’ decision to study at Politeknik LP3I Medan Kampus Baru. On the otherhand, pice had negative toward students’ decision toward students’ decision to study at Politeknik LP3I Medan Kampus Baru.